1984
DOI: 10.1288/00005537-198407000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Partial vs. total footplate removal in stapedectomy: A comparative study

Abstract: A comparative study of the postoperative stapedectomy results for 264 ears with partial footplate removal (PFR) and for 106 ears with total footplate removal (TFR) was performed with reference to decibel gain in three specific frequency ranges, air‐bone gap closure, speech threshold and speech discrimination and incidence of postoperative complications. The data confirm a small but consistently greater decibel gain for PFR cases in the 2000‐8000 Hz range; the decibel gain in the 250‐1000 Hz range is virtually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…Rosen in his original work had noted that occasional patients experienced a fenestration of the oval window without mobilization of the stapes and had dramatic hearing improvements, a phenomenon later studied by Fernandez et al 57 Interest returned to the concept of partial stapes footplate removal. Moon and Hahn 58 found that with a partial removal of the footplate there was a slight improvement in the hearing in the 2,000‐ to 8,000‐Hz results versus conventional stapedectomy. However, Robinson 59 found no difference between full and partial removal of the footplate using a Robinson prosthesis.…”
Section: History Of Stapes Surgerymentioning
confidence: 99%
“…Rosen in his original work had noted that occasional patients experienced a fenestration of the oval window without mobilization of the stapes and had dramatic hearing improvements, a phenomenon later studied by Fernandez et al 57 Interest returned to the concept of partial stapes footplate removal. Moon and Hahn 58 found that with a partial removal of the footplate there was a slight improvement in the hearing in the 2,000‐ to 8,000‐Hz results versus conventional stapedectomy. However, Robinson 59 found no difference between full and partial removal of the footplate using a Robinson prosthesis.…”
Section: History Of Stapes Surgerymentioning
confidence: 99%
“…Shea performed the first stapedectomy in 1956 [Shea, 1958] and introduced stapedotomy in 1960 [Shea et al, 1962]. The latter procedure has progressively become the treatment of choice for clinical otosclerosis due to a reduced risk of sensorineural hearing loss (SNHL) and better high-frequency gain [Shea, 1982;Fisch, 1982;Moon and Hahn, 1984;Causse et al, 1985;Kürsten et al, 1994;House et al, 2002;Vincent et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…With the evolution of stapes surgical techniques from the use of microinstruments for stapedectomies to the use of a microdrill and the use of lasers for stapedotomy, the risk of mechanical trauma is lower and the indications increasing. Since the early 1970s, the small-fenestra stapedotomy technique has become a standard because the procedure is less traumatic, reduces the risk of SNHL and provides better high-frequency gain [Fisch, 1982;Moon and Hahn, 1984;House, 1993;Somers et al, 1994]. The minimum ABG seen as an indication for footplate surgery varies among authors; it has been reported within the range of 35-40 dB [Glasscock and Shambaugh, 1990] and 25 dB or greater [Wiet et al, 1986].…”
Section: Introductionmentioning
confidence: 99%